Trinidad and Tobago : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper focuses on the impact of adjusting to commodity shocks in Trinidad and Tobago. With commodity resources being nonrenewable, developing a long-term strategy can help avoid unsustainable policies and ensure greater intergenerational equity. Recent country experiences highlight the benefits of precautionary buffers in smoothing fiscal adjustment process. Prudent and countercyclical fiscal policy implementation, structural reforms, and economic diversification can help contain the impact of commodity price booms and busts. Strong fiscal institutions are needed to help achieve and sustain the fiscal adjustment. Different adjustment strategies may be feasible depending on the needed size of the adjustment and country-specific circumstances. Trinidad and Tobago have faced several years of weak or negative growth on the back of terms-of-trade and energy supply shocks. A well-designed fiscal framework that considers potential uncertainties associated with commodity cycles can help improve fiscal management. Countercyclical policy implementation would help smooth the impact of commodity-induced sharp fluctuations in the economy.